Condensed Matter in a Nutshell. - Mahan, Gerald D. (In a nutshell., 2010)
Condensed Matter in a Nutshell is the most concise, accessible, and self-contained introduction to this exciting and cutting-edge area of modern physics. This premier textbook covers all the standard topics, including crystal structures, energy bands, phonons, optical properties, ferroelectricity, superconductivity, and magnetism. It includes in-depth discussions of transport theory, nanoscience, and semiconductors, and also features the latest experimental advances in this fast-developing field, such as high-temperature superconductivity, the quantum Hall effect, graphene, nanotubes, locali.